102 CLINICAL SIGNIFICANCE OF REACTIVE THROMBOCYTOSIS AFTER ACUTE MYOCARDIAL INFARCTION AND SUBSEQUENT STENT PLACEMENT: A RETROSPECTIVE CHART REVIEW. (1st January 2006) - Wilkerson, B.; Elkins, S.
Abstract : Background: During a recent month on hematology consults, 1 of 18 nonmalignant heme consults consisted of a patient with reactive thrombocytosis s/p acute myocardial infarction (AMI) and subsequent percutaneous coronary artery stent placement. The patient was noted to have a platelet count that rose to 1.3 million. At that time, a literature search was performed for reactive thrombocytosis after AMI and stent placement. Multiple articles were identified for essential thrombocythemia, but none for reactive thrombocytosis. The patient was treated with supportive care with normalization of platelet count and no adverse sequela during his hospitalization. The concern was for failure of coronary stent secondary to clotting from thrombocytosis and whether acute treatment for the thrombocytosis would be beneficial. This question would only be clinically relevant if the incidence of reactive thrombocytosis in this setting were of significant numbers to elicit a statistical comparison in outcome comparing normal to thrombocytosis patients. This article will review results from a retrospective chart review from patients with AMI and subsequent percutaneous coronary artery stent placement and the clinical significance of reactive thrombocytosis, if any. Methods: This is a retrospective chart review. Patients were selected from the University of Mississippi Medical Center hospital database based on diagnostic coding for AMI and percutaneous coronary artery stent placement. Patients were obtained from calendar year 2004. A platelet count of 600, 000 was arbitrarily chosen as a significant level. Results: 120 patients were identified with AMI and subsequent stent placement for calendar year 2004. Of those identified only one patient had a platelet count above the arbitrarily chosen significant level of 600, 000. That patient had a platelet count of 625, 000. This patient's outcome was not adversely impacted by the reactive thrombocytosis. It is felt by this review that reactive thrombocytosis after AMI/stent placement is rare and there is no apparent clinical significance of reactive thrombocytosis in the setting of AMI and subsequent percutaneous coronary artery stent placement regarding patient outcome or management.